When a large reserve is not large enough to protect part of a population: Blue-and-yellow Macaws (Ara ararauna) in central Brazil - Dárius Pukenis Tubelis (Biotemas)
This study aimed to examine movements of the Blue-and-yellow Macaw (Ara ararauna) across boundaries between the Parque Nacional das Emas and adjacent agricultural landscapes, in central Brazil. Two study sites were selected for observations conducted in October 2006 and February 2007. Groups of macaws were observed leaving the park and flying over extensive agricultural areas towards remnants of native vegetation, revealing resource use by these birds in the surrounding matrix. These observations suggest that conservation of part of the population of A. ararauna found at Emas National Park will require the expansion of this reserve and/or conservation actions by landowners in its surroundings.